Evaluating the Effectiveness of Iron Chelates in Managing Iron Deficiency Chlorosis in Grain Sorghum - A. Obour; A. Schlegel; R. Perumal; D. Ruiz Diaz (Kansas Agricultural Experiment Station Research Reports, 2016)
Grain sorghum production in alkaline or calcareous soils is frequently affected by iron (Fe) chlorosis. Soil conditions such as high pH, high free calcium carbonate (lime), and low organic matter favor development of Fe deficiency chlorosis (IDC), which can delay crop maturity and reduce yields. Field experiments were conducted in the summer of 2014 and 2015 to determine the effectiveness of Fe chelate application in alleviating IDC in grain sorghum. Treatments were four Fe chelate application rates (0, 3, 6, and 9 lb product/a) applied either in-furrow with the seed at the time of planting or 2 weeks after planting in 2014. A split treatment of 3 lb/a applied at planting and another 3 lb/a applied 2 weeks after planting was included. The study in 2015 had four Fe chelate rates (0, 3, and 6 lb product/a, and split treatment of 3 lb/a applied at planting and another 3 lb/a applied 2 weeks after planting) as main plots and five commercial sorghum hybrids as sub-plots. Results in 2014 showed IDC scores among the treatments were significant only in the early stages of growth. Iron chelate application did improve sorghum yield, with the highest yield occurring when Fe chelate was split-applied at 6 lb product/a. Grain sorghum hybrids differed in their response to IDC in 2015. Application of Fe chelates suppressed IDC and increased grain yield, particularly in susceptible hybrids in both dryland and irrigated sites. Our findings indicate that sorghum hybrids 86G32 and 87P06 showed promise for tolerance to IDC and that Fe chelate application to reduce IDC is economically feasible at current grain prices.
Keywords: Grain sorghum; iron deficiency chlorosis; Fe chelates